Pathway of anthracene modification under simulated solar radiation - Mallakin, Ali; George Dixon, D; Greenberg, Bruce M (Chemosphere (Oxford), 2000)
Exposure of polycyclic aromatic hydrocarbons (PAHs) to sunlight results in rapid structural photomodification generally via oxidation reactions. These PAH modification products are in many cases more toxic than their parent compounds. In this study, anthracene (ANT), a rapidly photooxidized PAH, was irradiated with simulated solar radiation (SSR, 100 μmol m −2 s −1) in aqueous solution to examine the photomodification pathway. The photoproducts formed were identified by HPLC. The ANT product profile after 9 h in SSR was very complex, with more than 20 compounds detected. The photoproducts formed were anthraquinones, benzoic acids, benzaldehydes and phenols showing the process to be oxidative in nature. Some of the anthraquinones were themselves subject to photooxidation, and were thus intermediates in the product pathway. The kinetics of ANT photooxidation revealed a pseudo first-order reaction with a half-life of 2 h under the SSR source used. The kinetics of product formation allowed deduction of a probable photomodification pathway. This study indicates that PAH photooxidation products are likely to exist as complex, dynamically changing mixtures in PAH contaminated aquatic environments.